PENGEMBANGAN MEDIA PEMBELAJARAN WORDWALL BERBASIS GAME BASED LEARNING UNTUK SISWA SEKOLAH MENENGAH ATAS - Annisa, Annisa Agustin; Sari, Raras Kartika (Universitas Insan Budi Utomo, 2025)
The updated learning process includes improving the quality of education through engaging teaching methods to make the learning atmosphere enjoyable. One way to make learning more effective and enjoyable is for educators to use learning media as a support for teaching and learning. Wordwall is a medium that can make students more interested in learning. Wordwall media based on Game Based Learning was used in research involving 11th grade students of class A.1 SMA in South Lampung. This research aims to delve into the influence of game-based learning on students' learning activities. The method applied is R&D (Research and Development) using the ADDIE model approach. The objective of developing the resulting learning tool product based on the Wordwall Game is designed to attract students' interest in learning mathematics. The results of the media expert feasibility validation test, which met the criteria and received a percentage of 94%, fall into the very feasible classification, while the subject matter expert validation test received an average of 88%, and the language expert validation test received an average percentage of 93%. Based on the trials, the Wordwall Game media is valid and suitable for use as an interactive learning aid in mathematics.